Value of systolic pulmonary arterial pressure as a prognostic factor of death in the systemic sclerosis EUSTAR population. (13th January 2015) - Hachulla, Eric; Clerson, Pierre; Airò, Paolo; Cuomo, Giovanna; Allanore, Yannick; Caramaschi, Paola; Rosato, Edoardo; Carreira, Patricia E.; Riccieri, Valeria; Sarraco, Marta; Denton, Christopher P.; Riemekasten, Gabriela; et al.
Abstract : Objective. The aim of this study was to assess the prognostic value of systolic pulmonary artery pressure (sPAP) estimated by echocardiography in the multinational European League Against Rheumatism Scleroderma Trial and Research (EUSTAR) cohort. Methods. Data for patients with echocardiography documented between 1 January 2005 and 31 December 2011 were extracted from the EUSTAR database. Stepwise forward multivariable statistical Cox pulmonary hypertension analysis was used to examine the independent effect on survival of selected variables. Results. Based on our selection criteria, 1476 patients were included in the analysis; 87% of patients were female, with a mean age of 56.3 years (s .d . 13.5) and 31% had diffuse SSc. The mean duration of follow-up was 2.0 years (s .d . 1.2, median 1.9). Taking index sPAP of <30 mmHg as reference, the hazard ratio (HR) for death was 1.67 (95% CI 0.92, 2.96) if the index sPAP was between 30 and 36 mmHg, 2.37 (95% CI 1.14, 4.93) for sPAP between 36 and 40 mmHg, 3.72 (95% CI 1.61, 8.60) for sPAP between 40 and 50 mmHg and 9.75 (95% CI 4.98, 19.09) if sPAP was >50 mmHg. In a multivariable Cox model, sPAP and the diffusing capacity for carbon monoxide (DLCO) were independently associated with the risk of death [HR 1.833 (95% CI 1.035, 3.247) and HR 0.973 (95% CI 0.955, 0.991), respectively]. sPAP was an independent risk factor for death with a HR of 3.02 (95% CI 1.91, 4.78) for sPAP ≥36 mmHg. Conclusion. An estimated sPAP >36 mmHg at baseline echocardiography was significantly and independently associated with reduced survival, regardless of the presence of pulmonary hypertension based on right heart catheterization.